Risk Factors for Six Types of Disability among the Older People in Thailand in 2002, 2007, and 2011 - Pattaraporn Khongboon; Sathirakorn Pongpanich; Robert S. Chapman (Journal of Aging Research)
Background. There is an important need to characterize risk factors for disability in Thailand, in order to inform effective prevention and control strategies. This study investigated factors associated with risk of 6 types of disability in Thailand’s ageing population in 2002, 2007, and 2011. Methods. Data came from the Cross-Sectional National Surveys of Older Persons in Thailand conducted by the National Statistical Office (NSO) in 2002, 2007, and 2011. Stratified two-stage sampling was employed. Interviews of 24,835, 30,427, and 34,173 elderly people aged 60 and above were conducted in the respective study years. Prevalence of disabilities was measured, and factors associated with disability risk were assessed with probability-weighted multiple logistic regression. Results. Disability prevalence decreased slightly over the study period. The characteristics with greatest positive impact on disability prevalence were not working over the past week (average impact: 61.2%), age (53.7% per decade), and suffering from one or more chronic illnesses (46.3%). Conclusions. The strong observed positive impact of not working on disability prevalence suggests that raising the mandatory retirement age might result in some reduction of disability risk. Also, the observed positive impact of living with others (versus alone) on disability risk was somewhat unexpected.